(untitled) (Scientific journal of the Fergana State University, 2026)
This article presents an analysis of the research results aimed at determining the distribution of species of the genus Scutellaria (Lamiaceae) within various phytocoenotic types in the Fergana Valley. Data are provided on the occurrence of species of the genus within the petrofilous phytocoenotic group, including xerohazmophytic, xerolithophytic, and cryopetrophytic types.